Tape lures swell bycatch on a Mediterranean island harbouring illegal bird trapping. (30th September 2020) - Sebastianelli, Matteo; Savva, Georgios; Moysi, Michaella; Kirschel, Alexander N. G.
Abstract : Mediterranean islands provide shelter and sustenance for millions of migrating birds each year. Humans have historically exploited bird migration through hunting. In Cyprus, trapping birds during their migratory peak is considered a tradition, but has long been against the law. Illegal bird trapping is lucrative, however, with trappers using tape lures that broadcast birdsong to increase capture rates. It results in the slaughter of millions of birds each year. Yet, scientific studies quantifying capture rates of target and nontarget species using methods employed by trappers are lacking. Here, we show using playback experiments that tape lures lead to an order of magnitude greater capture rates of target species, but also significantly increase bycatch, which may include species of conservation concern. Conservation efforts focusing on minimizing illegal bird killing should also consider tape lures and their contribution to the overall impact of trapping on avian populations.